Cryospheric Impacts on Volcano-Magmatic Systems - Edwards, Benjamin R.; Russell, James K.; Pollock, Meagen (Frontiers in Earth Science, 2022)
In contrast to water and air, ice is the most dynamic enveloping medium and unique environment for volcanic eruptions. While all three environments influence volcanic activity and eruption products, the cryospheric eruption environment is unique because: i) it supports rapid changes between those environments (i.e. subglacial, subaqueous, subaerial), ii) it promotes a wide range of eruption styles within a single eruption cycle (explosive, effusive) , iii) it creates unique edifice-scale morphologies and deposits, and iv) it can modulate the timing and rates of magmatism. The distinctive products of cryospheric eruptions offer a robust means of tracking paleoclimate changes at the local, regional and global scale. We provide a framework for understanding the influence of the cryosphere on glaciovolcanic systems, landforms and deposits.